An improvement of storage space and drying using shoe dryer cabinet / Muhammad Arif Imran Iskandar - Iskandar, Muhammad Arif Imran (2023)
Shoes that dried in the sun may take a long time to dry and may be affected by the weather. People nowadays does not have proper storage to place their shoe from any circumstances such as getting wet by rain, being dirt by their pets, getting dust. The goal of this design is to make it simple for people to dry and stores their shoes. A shoe dryer has been devised as a solution to this problem. The design of this mobile shoe dryer, which is light and portable, may give some convenience in terms of drying shoes anyplace. Because the shoe dryer is meant to be a medium-sized item, it is portable and easy to transport. The cabinet she dryer can take below than 3hours to completely dry wet shoe. This cabinet is very potential for people who did not want to wait until day to dry their shoes and to people who want to arrange their shoes in a proper storage. Then, Shoe Dryer Cabinet was created to solve these issues.